2019
DOI: 10.1177/0954008319839442
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of graphene/polyaniline nanocomposite by in situ intercalation polymerization and their application in anti-corrosion coatings

Abstract: This study reports a strategy for further simplifying the synthesis process of polyaniline-modified graphene (An/G) nanocomposite. For this purpose, the An/G nanocomposite was prepared by expanded graphite (EG) and aniline (An) via in situ polymerization. The structures and morphologies of the An/G nanocomposite were examined by Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, ultraviolet–visible spectroscopy and ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Cui et al 101 examined the BN effect on the epoxy coating's performance of anti‐corrosion. The Poly (butylamine‐2)‐(PBA) was utilized yet again in easing the dispersion and exfoliation BN nanosheet and the behavior of corrosion of the epoxy coatings were characterized.…”
Section: The Corrosion Properties Of Epoxy Nano‐filled Compositesmentioning
confidence: 99%
“…Cui et al 101 examined the BN effect on the epoxy coating's performance of anti‐corrosion. The Poly (butylamine‐2)‐(PBA) was utilized yet again in easing the dispersion and exfoliation BN nanosheet and the behavior of corrosion of the epoxy coatings were characterized.…”
Section: The Corrosion Properties Of Epoxy Nano‐filled Compositesmentioning
confidence: 99%
“…The high electrical conductivity of pristine graphene or RGO enables fast charge transport and prevents corrosion. Li et al 31 prepared PANI-modified graphene composites by expanded graphite and aniline monomers via in situ polymerization. The anti-corrosion performance of the EP coating with 2 wt % PANI-modified graphene composites was evaluated and exhibited significant improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a typical 2D material with exciting fascinating features such as the highest strength and Young's modulus ever measured, gigantic specific surface area, best-known thermal conductivity, and electrical conductivity, which is an ideal filler for high-performance multifunctional nanocomposites in light of its superior mechanical, electrical, thermal, and optical properties [5]. Graphene polymer composites with high performance are applied in sensors [6], actuators [7,8], energy storage [9], and absorbing and protective coating [10,11]. Trajcheva, A. et al [6] proposed a waterborne polymer/Graphene Nanoribbon nanocomposites for low concentrations of toxic gases detection (CO, NH 3 , and N 2 O in a concentration range of 70-1000 ppm), it was found that the sensors are characterized by a large sensor response in a short time, at room temperature and with very good reproducibility in three investigated cycles of gas adsorption and desorption; Panahi-Sarmad, M. et al [7] reviewed the latest progress and potential application scenarios of graphene actuators; James Loomis et al [8] prepared nanoplatelet/polydimethylsiloxane (PDMS) composites as photomechanical actuators and studied their infrared (IR) mechanical responses with increasing pre-strains; Li et al [11] prepared polyaniline modified graphene nanocomposites as anti-corrosion coatings and showed good anti-corrosion effects.…”
Section: Introductionmentioning
confidence: 99%